2005
DOI: 10.1081/pfc-200047576
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Waste Activated Carbon on Atrazine Removal from Contaminated Water

Abstract: In this study, the potential of spent activated carbon from water purifier (Aqua Guard, India) for the removal of atrazine (2 chloro-4 ethylamino-6-isopropylamino-1, 3, 5 triazine) from wastewaters was evaluated. Different grades of spent activated carbon were prepared by various pretreatments. Based on kinetic and equilibrium study results, spent activated carbon with a grain size of 0.3-0.5 mm and washed with distilled water (designated as WAC) was selected for fixed column studies. Batch adsorption equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…However, high cost of activated carbon encourages using of low cost and/or waste materials as adsorbent for various pollutant removals from aqueous environment [22][23][24][25][26][27]. It has been reported that surface modification with suitable chemicals and impregnation techniques not only increase adsorption capacity but also add selectivity to carbon [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, high cost of activated carbon encourages using of low cost and/or waste materials as adsorbent for various pollutant removals from aqueous environment [22][23][24][25][26][27]. It has been reported that surface modification with suitable chemicals and impregnation techniques not only increase adsorption capacity but also add selectivity to carbon [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, a 2 % MR observed at 4 kOe still indicates that this GMR sensor could be used for biological targeting application. 23 An initial adsorption test shows that the heat-treated nanocomposite has a fairly high porosity adsorbing about 7 wt% of argon; indicating that this composite can be used for water distillation, 24 as well as for tail gas catalysis or hydrogen storage 25 for fuel cell applications.…”
mentioning
confidence: 99%
“…Studies conducted to enhance the degradation rate by addition of readily biodegradable organic amendments showed that, although acetic acid enhanced the biotransformation from the parent compounds to hydroxyatrazine, only glucose improved the removal rate of the triazine species [95]. Ghosh and Philip [101] observed the effects of external carbon source on atrazine degradation by mixed culture anaerobic bacteria. In co-metabolic process (dextrose was the primary source of carbon and energy), there is certain ratio of primary substrate and the toxic compound, at which the degradation of atrazine was the maximum.…”
Section: Effects Of External Carbon Source On Atrazine Biodegradationmentioning
confidence: 99%
“…Studies on atrazine adsorption on iron oxides [99], quartz, calcite, kaolinite and α-alumina [100] showed that only kaolinite was suitable for the adsorption of atrazine. It has been reported that waste activated carbon (WAC) from tap water purifier can be used for post treatment of upflow anaerobic sludge blanket (UASB) reactor effluent [101].…”
Section: Adsorptionmentioning
confidence: 99%